Study on Calibration Tests for Interface-Type Earth Pressure Cell Based on Matching Error Analysis - Mingyu Li; Longwei Zhu; Jicheng Shu; Zhenzhen Lu; Yunlong Liu (Sensors)
The stress status of a soil pressure cell placed in soil is very different from its stress state in a uniform fluid medium. The use of the calibration coefficient provided by the soil pressure cell manufacturer will produce a large error. In order to improve the measurement accuracy of the interface-type earth pressure cell placed in soil, this paper focuses on a single-membrane resistive earth pressure cell installed on the surface of a structure, analyzing the influence of loading and unloading cycles, the thickness and particle size of the sand filling, and the depth of the earth pressure cell inserted in the structure on the calibration curve and matching error, which were analyzed through calibration tests. The results show that when the sand filling thickness is less than D (D is the diameter of the earth pressure cell), the calibration curve is unstable in relation to the increase in the number of loading and unloading cycles, which will cause the sand calibration coefficient used for stress conversion to not be used normally. When the sand filling thickness in the calibration bucket increases from 0.285D to 5D, the absolute value of the matching error first decreases and then increases, such that the optimal sand filling thickness is 3D. The output of the earth pressure cell increases with the decrease in sand particle size under the same load, and there is a significant difference between the theoretical calculation value and the experimental value of the matching error; aiming at this difference, an empirical formula is derived to reflect the ratio of the diameter of the induction diaphragm of the earth pressure cell to the maximum particle size of the sand filling. When the depth of the earth pressure cell inserted in the structure is “0”, the sensing surface is flush with the structure and the absolute value of the matching error is the smallest. Changes in the horizontal placement of the soil pressure cell in the calibration bucket result in significant differences in both the output and hysteresis of the calibration curve. To improve the measurement accuracy of soil pressure cells in scaled tests for applications such as in the retaining walls of excavation pits, tunnel outer surfaces, pile tops, pile ends, and soil pressure measurements in soil, calibration of the soil pressure cells is required before testing. Due to the considerable difference in the stress states of the soil pressure cell between granular media and uniform fluid media, calibration in soil is essential. During in-soil calibration, factors such as cyclic loading and unloading, soil compression, sand thickness and particle size, and the placement of the soil pressure cell all affect the calibration results. This paper primarily investigates the influence of these factors on the calibration curve and matching error. This study found that, as the sand thickness increases, the matching error decreases initially and then increases.